The Implementation of the Cascading Method in Post-COVID-19 English Language Learning at SDN 3 Timpag Tabanan - Kuntariati, Utik (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
As of COVID-19, instruction methods are once again being optimized through enticing education, which has been going strong for the past year. Every institution of higher learning that exists in Indonesia, from elementary schools to universities, is targeted by offline learning. SDN 3 Timpag Kabupaten Tabanan is the only primary school now operating under an offline curriculum. But as of right now, SDN 3 Timpag is experiencing a few setbacks, particularly when it comes to the implementation of the teaching method for students who previously studied using the online learning method. The research uses a qualitative approach as a method of analysis. The term "qualitative research" refers to research that uses non-angular literature and data as a component of the study. The current study makes use of literary research studies and analysis related to the current phenomenon. Studying literature is one method that encourages researchers to collect data through reading a variety of documents, printed and digital. The research findings that would be made are related to the objectives of the use of the Cascading model of instruction for the students at SDN 3 Timpag. The cascading learning model is organized using five stages, including formulating cascading materials, orientation, grouping, determination of materials, presentation, and evaluation. These five stages play a crucial role in the development of the learning system at SDN 3 Timpag, especially in shaping students' perspectives related to tourism objects to be integrated into English language learning materials. In addition, the researcher conducted a SWOT analysis, where it was found that the internal threat factor is students who have not been able to adapt to the new learning model, and the external factor is students who have experienced learning loss and will find it more challenging to develop creative thinking skills.